(untitled) (Journal of Bangladesh Institute of Planners, 2019)
Dhaka, the capital of Bangladesh and 8th largest mega city in the world, is the home of more than twenty million people with its sprawling slums and dense suburban areas. Ecologically critical areas like agricultural land, wetland and other water bodies in the urban fringe areas are quickly vanishing from the landscape of Dhaka city to meet up the overarching demand of growing urban population. Land readjustment (LR), an urban land use management technique is widely used for carefully handling the development of fringe areas which are potentially ripe for new urban expansion at no or minimum cost to the government. In view of the above, this research has tended to focus on the aptness of Land Readjustment techniques for orderly urban expansion and fringe area development of Dhaka city along with the aim of conserving ecologically critical areas. The study used data both from primary and secondary sources to accomplish the purposes. The study argues the role of Land Readjustment technique in ensuring issues vis-à-vis integration of social security, economic feasibility and disaster risk reduction while tackling the great sustainability challenge for reshaping the city. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 109-120